SAE Technical Paper Series 2018
DOI: 10.4271/2018-01-1765
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermocouple Size on the Measurement of Exhaust Gas Temperature in Internal Combustion Engines

Abstract: Accurate measurement of exhaust gas temperature in internal combustion engines is essential for a wide variety of monitoring and design purposes. Typically these measurements are made with thermocouples, which may vary in size from 0.05 mm (for fast response applications) to a few millimetres. In this work, the exhaust of a single cylinder diesel engine has been instrumented both with a fast-response probe (comprising of a 50.8 μm, 127 μm and a 254 μm thermocouple) and a standard 3 mm sheathed thermocouple in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…In terms of exhaust temperature, marginal increases were also observed with the SC piston with the biggest differences observed for the TP1 case (~7 °C). This translates into an increase in exhaust enthalpy of ~0.5 %, however considering the inherent errors associated with temperature measurement in internal combustion engines, the authors expect these gains to be underestimated [25].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of exhaust temperature, marginal increases were also observed with the SC piston with the biggest differences observed for the TP1 case (~7 °C). This translates into an increase in exhaust enthalpy of ~0.5 %, however considering the inherent errors associated with temperature measurement in internal combustion engines, the authors expect these gains to be underestimated [25].…”
Section: Discussionmentioning
confidence: 99%
“…It is seen that the use of the steel piston design results in consistent, small (~1.3 to 2.5%), but statistically significant decreases in mean exhaust gas temperature. A note on the detail of these exhaust temperature measurements is included in [25]. Table 3 details the changes in ignition delay, early phase combustion duration (10 -50% MFB), late phase combustion duration (50 -90% MFB) and the overall combustion duration (10 -90% MFB) for the steel piston relative to the aluminium.…”
Section: Resultsmentioning
confidence: 99%
“…This process has two caveats; first, the sensor indicates the tempera e f he he c e j c i a d he f id temperature which will be lower due to conduction and radiation heat transfer away from the junction. The effects of conduction and radiation errors in ICEs have been the subject of many studies in the past [11][12][13][14][15][16]. Figure 1 shows the various heat transfer modes that a thermocouple junction is exposed to when installed on the exhaust pipe of an ICE.…”
Section: Introductionmentioning
confidence: 99%
“…This schematic assumes that the gas is at a higher temperature than the junction and the wall at a lower temperature. This is not always the case and simulations have shown that during the period that the exhaust valves are closed, the junction can be at a higher temperature than the surrounding gas [15]. Papaioannou et al…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation